SELF INCOMPATIBILITY PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) - Nurhermawati, Renica; Supena, Nanang; Arif, Mohamad (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2024)
Self-incompatibility (SI) is a genetic mechanism which prevents self-pollination and encourages plant cross-pollination, but the mechanism has not been studied on oil palm. The article examines possibilities of SI mechanisms on oil palm which cause pollination failure. References which were published nationally (S2-S3) and internationally (Q1-Q4) were utilized. In general, plants have two types of SI: heteromorphic self-incompatibility (HetSI) and homomorphic self-incompatibility (HomSI). HetSI is caused by plants having morphologically different flower types, while HomSI occurs when plants have morphologically similar flowers. However, an SI mechanism is still regulated at the genetic level. Homomorphic SI can also be divided into two types based on the genetic determinants of pollen incompatibility: Gametophytic Self Incompatibility (GSI) and Sporophytic Self Incompatibility (SSI). In GSI, the SI mechanism is controlled by the genotype of the pollen itself, which is haploid, while in SSI, it is determined by the genotype of the plant tissue (sporophyte) that produces the pollen and is diploid. The S-locus regulates both types of SI with different mechanisms. In seedless oil palm plants, S-RNAse was found to play a role in the degradation of pollen tubes, SRK (S-receptor kinase), and SLG (S-locus glycoprotein), which are genes that regulate the HomSI mechanism in several plants. The presence of S-RNAse and genes in the S-locus raises the possibility of an SI mechanism in oil palms that produce seedless fruit. In addition, a mechanism of stenospermy and endosperm tissue abnormalities is thought to produce fruit with sterile seeds (without embryos) in oil palms. However, it is still being determined whether both are part of the SI response or not. So, further studies are needed to confirm this and give the new perspectives